MCSim-Based Occupational Health Risk Assessment on Benzene - Minyan Li; Deyin Huang; Mao Liu (Journal of Risk Analysis and Crisis Response (JRACR), 2013)
Nowadays, the acute and chronic adverse health effects caused by benzene exposure have attracted wide attention. In this paper, we evaluate the health risk based on the four-step method recommended by U.S. Environmental Protection Agency (USEPA). We present a method using the Monte Carlo Simulating Software (MCSim) to build a PBPK model to simulate the concentrations in target tissues of human in distribution forms. The internal dose will be used in the dose-response model to figure out the cancer risk. In the case of workers exposed to benzene in oil refinery workplace, we take the advantage of FLUENT software to simulate the external dose, treat the concentration data by SPSS, and compute the internal dose by MCSim software, so that the lifetime cancer risk range of exposed workers can be calculated if the benzene occupational exposure scenarios are complicated. This method will be used to provide the basis for the occupation health management of enterprises.